Sustainable gardens for smart cities using low-power communications - Mota, B. da.; Mataloto, B.; Coutinho, C. (2022 IEEE 28th International Conference on Engineering, Technology and Innovation (ICE/ITMC) & 31st International Association For Management of Technology (IAMOT) Joint Conference, 2022)
This paper presents a study on smart gardens in the context of smart cities, a topic that has been gaining more and more interest from the public due to the numerous problems that are felt both in terms of the environment and in terms of food consumption which, due to population increase and migration towards cities, has become a sustainability problem as agricultural production is moving further away from the consumers thus making it harder to obtain fresh good such as fruits and vegetables. Using IoT combined with communication technologies such as LoRa that have Low-power and wide-area network capabilities, it is possible to create systems that enhance sustainability through a more efficient use of resources while also making its users be more involved with the plant cultivation process and, therefore, develop more empathy towards this topic and nature in general. Several smart garden systems and contexts in which those systems are implemented will be analyzed to understand what can be done within this research field.